Power imbalances and socio-demographic barriers in robusta coffee value chain: Insights from Malang Regency, Indonesia - Hadi, Yuswono; Soemarno, Soemarno; Dania, Wike Agustin Prima; Astuti, Retno (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
This study investigated power imbalances and inefficiencies in the Robusta coffee value chain in Malang Regency, Indonesia, employing an integration of the Structure-Conduct-Performance (SCP) framework and Value Chain Analysis (VCA). As the world’s fourth-largest coffee producer, Indonesia’s sector relied on smallholder farmers, who constituted 98% of producers but faced systemic marginalization. Drawing on survey data from 2,122 smallholder farmers and interviews with 26 traders, the analysis revealed a highly concentrated market structure, with four local collectors controlling 58% of trade and a single exporter dominating 68% of production. Farmers, despite generating 89% of value-added, retained only 50% of the consumer price due to exploitative intermediaries and informal pricing. Socio-demographic challenges, such as an aging workforce (92.5% over 45 years) and gender disparities (8.33% female participation), further hindered innovation and equity. The SCP-VCA integration uniquely exposed how market concentration enabled intermediaries to externalize costs, capturing 45.7% of the consumer price as profit, while farmers bore disproportionate labor. Policy implications emphasized digital transparency tools, farmer cooperatives, and certification subsidies to rebalance power dynamics. Demographic reforms, including youth engagement programs and gender-inclusive governance, were critical to addressing structural vulnerabilities.